The Relationship between Weight‐Based Prejudice and Attitudes towards Obesity‐Reducing Public Policies. Issue 1 (5th May 2016) - Berg, Michael B.; Lin, Linda; Hollar, Sara M.; Walker, Samantha N.; Erickson, Lauren E.
Abstract : A variety of public policies have been proposed to counteract obesity. Many factors, such as the desire to promote better health, may affect the support for such policies. However, given the pervasiveness of weight‐based prejudice in the United States, it is likely that antifat bias may influence policy attitudes as well. We predicted that higher levels of weight‐based prejudice would be positively associated with attitudes towards obesity‐reducing policies and would be associated specifically with support for policies that are more punitive in nature. In two separate studies, participants were surveyed about their level of support for various public health polices and their explicit antifat prejudice attitudes, along with other relevant attitudinal and demographic information. Study 1 established that weight‐based prejudice was significantly associated with support for more punitive policies even when controlling for other related factors. Study 2 extended this result to show that the link between antifat attitudes and support for punitive policies was foremost about targeting overweight individuals as opposed to targeting unhealthy behavior. These findings highlight the need for thoughtful consideration of how best to separate out the prejudicial motive to punish from the need to promote health when choosing, garnering support for, and implementing obesity‐related policies.